Unstable mixing regions in II-VI quaternary solid solutions - Deibuk, V.G.; Dremlyuzhenko, S.G.; Ostapov, S.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The miscibility gaps and critical temperatures of the spinodal decompositions of the quaternary semiconducting epitaxial thin films CdMnHgTe and ZnMnHgTe have been calculated. Fitting the spinodal isotherms calculated from the free energy of mixing being based on application of the delta-lattice parameter method to the experimental data, the model constant K is determined. It has been shown the narrowing of the spinodal decomposition regions due to both the deformation energy and the effect of plastic relaxation caused by mismatch dislocations in thin films.